A newly composed paraffin encapsulated prototype roof structure for efficient thermal management in hot climate. (1st June 2016) - Akeiber, Hussein J.; Wahid, Mazlan A.; Hussen, Hasanen M.; Mohammad, Abdulrahman Th.
Abstract: For efficient thermal management in the building under hot weather condition a new paraffin composition as suitable PCM is needed. Several notable attributes of paraffin wax including thermo-physical properties, open air atmospheric condition, economy, and environmental amiability make them suitable PCM for incorporation in the building. Thus, new PCM with massive storage of heat or cold in a specific volume is demanded. Iraqi local paraffin waxes as PCM are proven to be highly prospective due to their high-vitality thickness and isothermal conduct. However, thermal performance optimization of new PCM is pre-requisite to determine its effectiveness in hot climate location. We prepare three new PCM compositions with different oil to wax ratios from the crude petrochemical feed stock waste using fractionation followed by de-waxing and crystallization. The melting temperatures and flash points of these paraffin waxes are ranged between 19 and 44 °C and 177–256 °C, respectively, which upon encapsulation in the prototype roof construction are demonstrated to produce thermal comfort in rooms under hot climate (Iraq). Furthermore, these indigenous PCMs (local paraffin) are abundant, environmental friendly, economic and save electricity cost and HVAC (heating-ventilating air conditioning) systems. Experimental results displayed much reduced temperature fluctuation and internal heat flux of the prototype room than the commercial PCMs. Temperature profiles and solar irradiances inside the room on hot summer days in Bagdad showed remarkable electricity saving. This newly extracted PCM being non-flammable and thermally comfortable are truly secure for buildings construction worldwide. Highlights: A new composition of paraffin as PCM wax is extracted from local crude oil waste. This PCMs have wide range melting temperature and then available commercially. Local paraffin can reduce the internal heat flux and temperature fluctuation. PCM with superior thermal performance is highly suitable in hot climatic condition.